Risk factors for anti tuberculous drugs induced hepatitis: a prospective survey from a chest clinic in a general hospital - Abdul Rani, Mohammed Fauzi; Rathor, Mohammad Yousuf; Mohd Shah, Azarisman Shah; Satwi, Sapari (Malaysian Medical Associations, 2004)
A prospective survey on 14 consecutive cases with tuberculous drug induced hepatitis was done at our chest clinic in a state general hospital over a period of 15 months. There were 30 controls chosen randomly from the chest clinic register. The cases had lower mean body mass index (P<0.008), serum albumin (P<0.005) and higher serum globulin (P<0.04). Serum liver transaminases and total bilirubin rose significantly during the acute episode of drug induced hepatitis. Among the risk factors studied, only chronic hepatitis B carrier status was found to be more prevalent among the cases. There was one death (7.1%) over the whole study period.